Extending decision making competence to special populations: a pilot study of persons on the autism spectrum - Levin, Irwin P.; Gaeth, Gary J.; Foley-Nicpon, Megan; Yegorova, Vitaliya; Cederberg, Charles; Yan, Haoyang (Frontiers in Psychology, 2015)
The area of decision making has much to offer in our effort to understand special populations. This pilot study is an example of just such a project, where we illustrate how traditional decision making tools and tasks can be used to uncover strengths and weaknesses within a growing population of young adults with autism. In this pilot project we extended accounts of autistic behavior such as those derived from “theory of mind” to predict key components of decision making in high-functioning young adults on the autism spectrum. A battery of tests was administered to 15 high-functioning college students with autism spectrum disorder (ASD), focusing on Decision Making Competence (DMC) and other aspects of decision making related to known deficits associated with autism. Data from this group were compared to data from unselected college students receiving the same measures. First, as a test of a key social deficit associated with autism, the target group scored much lower on the Empathy Quotient scale. Traditional elements of decision making competency such as Numeracy and application of decision rules were comparable across groups. However, there were differences in thinking style, with the ASD group showing lesser ability and engagement in intuitive thinking, and they showed lower levels of risk taking. For comparisons within the ASD group, autobiographical reports concerning individual lifestyles and outcomes were used to derive a scale of Social Functioning. The lowest scoring individuals showed the lowest levels of intuitive thinking, the lowest perceived levels of others' endorsement of socially undesirable behaviors, and the lowest ability to discriminate between “good” and “bad” risks. Results are discussed in terms of interventions that might aid high-functioning young adults with ASD in their everyday decision making.